Wisdom in the Digital Era: Bridging Human Rights, Indonesian Cyber Law, and Progressive Fiqh - Iffatin Nur; Indri Hadisiswati; Hiba Fajarwati; Haniefa Nuruddienil Fithriy; Muhammad Diyaulhaq Rais (The Journal of Society and Media, 2026)
Digital technologies have reconfigured the landscape of public discourse, religious expression, and civic participation, generating both democratic opportunities and profound ethical challenges. While existing legal frameworks seek to regulate harmful online behavior, law alone proves insufficient to cultivate responsible digital conduct. This article argues that wisdom (ḥikmah) constitutes a critical, yet under- explored, ethical capacity for navigating the digital public sphere. Employing a normative–philosophical legal methodology, this study integrates three normative traditions: international human rights law, Indonesia’s Electronic Information and Transactions Law (EIT Law/UU ITE), and Progressive Fiqh grounded in maqāṣid al-sharī’ah, maṣlaḥah, and istiḥsān. Through conceptual and comparative analysis, the article demonstrates how wisdom functions as a mediating moral rationality that harmonizes freedom of expression with human dignity and social responsibility. The findings propose a model of “digital wisdom” that shifts governance from reactive legal control toward anticipatory ethical responsibility. This framework contributes to contemporary debates on digital governance, Islamic legal theory, and human rights by offering a culturally grounded yet universally resonant model of ethical digital citizenship. Future studies are encouraged to empirically examine how wisdom-based ethical frameworks can be institutionalized through digital literacy education, judicial practice, and religious discourse in diverse socio-legal contexts